Applicability of Static Analysis for Fracture Characterization of 3D Elliptical Disc Crack Under Dynamic Impact Loading - Sun Zhufeng; Abd Rahim, Inzarulfaisham; Ooi Lu Ean; Yusoff, Norwahida (Applications of Modelling and Simulation, 2025)
Engineering and industrial structures, such as pressure vessels, power plants, and offshore platforms, may develop defects like cracks and corrosion during manufacturing and service life. These defects significantly affect the dynamic load response of the structure, complicating the prediction of the structure’s carrying capacity and the accuracy of risk assessments. Due to this complexity, characterizing the dynamic stress intensity factor is challenging. Therefore, it is necessary to understand the dynamic response of defective structures. This study aims to analyze the dynamic fracture mechanics of a buried three-dimensional elliptical disc crack using finite element analysis by examining the stress response under dynamic impact loads. The influence of the crack geometry of the elliptical disc crack on the structural strength of different materials; aluminum alloy, stainless steel and cast iron, was further examined and compared with static analysis. The results of finite element analysis show that under impact load, when the elliptical disc crack is relatively small and the structure’s dimension can be considered infinitely large, the crack geometry noticeably affects the stress distribution and stress magnitude the crack tip, which is consistent with the mathematical deduction. Under the same dynamic loading and crack geometry conditions, brittle cast iron is more sensitive to dynamic impact than stainless steel and aluminum alloy, with stress magnitudes in cast iron also a little higher than those in the other two materials. Stress analysis of the crack tip further reveals that the distribution of stress field under impact load is similar to that under static load, and the maximum principal stress under dynamic impact load is lower than that under static load for all three materials. Based on these findings, the static maximum principal stress analysis can sufficiently be used to characterize fracture properties of three-dimensional cracked bodies under dynamic impact loading and reduce the workload associated with the dynamic analysis.